SERVICE EXCELLENT PEDIATRIC NURSING CARE MANAGEMENT ON AN. A WITH ACUTE RESPIRATORY TRACT INFECTION (ARI) IN ROOM RB 4 RSUP H. ADAM MALIK CITY MEDAN NORTH SUMATRA YEAR 2025 - Tania Aryodila; Petra Diansari Zega; Rolasnih Lilista Simbolan; Edi Subroto; Juni Arman Sianturi; Nurul Ainun Zahro Br surbakti; Indah Muliana Br Girsang, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Acute Respiratory Tract Infections (ARI) remain a leading cause of morbidity and mortality among children in Indonesia. These cases are often exacerbated by environmental factors such as air pollution, cigarette smoke exposure, poor ventilation, and low immunization coverage. This study aims to implement nursing care management for children with a service excellent approach in treating a pediatric ARI patient in the Rindu B4 ward of H. Adam Malik General Hospital, North Sumatra. The study employed a descriptive case study method on a 13-year-old patient (An.A) diagnosed with ARI. Data were collected through interviews, observation, and document analysis. Nursing care was administered through a comprehensive process, including assessment, diagnosis, planning, implementation, and evaluation. Results showed significant improvements in the patient's condition following interventions in airway management, hyperthermia control, and nutritional support. The service excellent model based on the PACER principles (Professionalism, Accountability, Collaboration, Empathy, and Reliability) proved effective in enhancing care outcomes and family satisfaction. This study recommends strengthening family education and interprofessional collaboration to reduce ARI incidence and improve the quality of pediatric nursing care in hospital settings.